(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The main aim of the study is to study the trade-off between liquidity and profitability byanalysing the adequacy of working capital in private sector banks and forward relevant suggestions andrecommendations regarding Working Capital Management and highlight the relevance of internalfinancing on performance of private sector banks. It is concluded that the findings of the model estimatesuggest that there is a strong negative correlation and causal link between the ratios of total debt tocapital and long-term debt to capital, and the financial performance indicators of banks, namely Returnon Assets, Return on Equity, and Earnings per Share